Construction of two-dimensional molybdenum carbide based electrocatalyst for real-time monitoring of parathion-ethyl. Issue 6 (December 2021) - Kokulnathan, Thangavelu; Wang, Tzyy-Jiann; Ahmed, Faheem
Abstract: Parathion-ethyl (PE) is an organophosphate insecticide frequently used in modern agriculture to enhance food quality. The extensive usage of PE causes ecological damage to the environment and a fatal threat to human health. Therefore, it is essential to develop practical tools for assessing the PE content in aquatic samples. In this study, a flexible electrochemical sensor based on molybdenum carbide (MoC) is developed for the sensitive and selective detection of PE. The MoC properties were characterized using X-ray diffraction, field emission scanning electron microscopy, transmission electron microscopy, elemental mapping, and energy-dispersive spectrometry. The electrochemical sensor based on MoC shows excellent electrocatalytic activity to the reduction of PE compared to the unmodified electrode. The improved electrocatalytic activity results from the two-dimensional MoC structure, good conductivity, large surface area and numerous active sites. The proposed electrochemical sensor exhibits an ultralow limit of detection (0.004 μM), a wide linear range (0.02–43 μM), and striking sensitivity (10 μA µM –1 cm –2 ). Besides, the MoC based electrochemical sensor demonstrates good stability, excellent anti-interference property, high reproducibility, storage stability and good suitability in aquatic samples. These results indicate that the proposed MoC based sensor can provide a promising strategy to monitor the content of PE in the environmental samples with high efficiency and low interference. Graphical Abstract: ga1 Highlights: A highly sensitive and selective electrochemical sensor is developed based on the MoC for parathion-ethyl (PE) detection. The electrochemical detection of PE achieves a wide linear range, low LOD and high sensitivity. The practical application is demonstrated by the detection of PE spiked in the water samples.